(untitled) (diségno, 2023)
Drawings represent ideas and concepts, not just an architectural project. The concept of the ‘Architecture of the Crowd’ establishes principles of an architecture in which people are protagonists. This architecture, in turn, relates in a harmonious way to the city, inviting people to enter, circulate, and interact with the space and other people, in a natural way. Fábio Moura Penteado’s architectural drawings representing these ideas and concepts were the focus of this study. The projects selected for analysis, dating back to the 1960s, are as follows: Araras Forum (1960), Campinas Coffee Museum (1960), Piracicaba Municipal Theater (1961), Campinas Opera Theater (1966), Campinas Cultural Coexistence Center (1967). Through the analysis of handmade perspective drawings, we can identify the presentation of ideas contained in their theoretical and conceptual discourse. The elements that define and compose the drawings are significant for the representation of their ideas: points of view from which the drawing was constructed; number of people, interacting, immobile or moving, and their location; automobiles and machinery; vegetation and landscape; representation of the accesses to the building with some welcoming element such as a marquee; indication of paths and routes. A point of view that has the ambition of a good, urban, modern society, from the perspective of ordinary people roaming the city and promoting meetings and events in a democratic, safe, and healthy environment.